A Bridge from Fools: Using the Motley Fool Money Podcast to Link Classroom Concepts to Real World Relevance. - Engel, Russell (Journal of Applied Business & Economics, 2019)
Keywords: dept.acc; peer-reviewed; ⛔ No DOI found

Cryptocurrencies for the payment of products or services: Risks, accounting practices and regulations - Allen, David; Aselta, James; Engel, Russell (Accounting and Finance Research, 2019)
This paper examines the risks, accounting practices and disclosures of companies who accept cryptocurrency for the payment of products or services. We provide a brief history of cryptocurrency and blockchain technology that allows the reader to deepen their understanding of the subject before moving on to a discussion of how regulatory bodies such as the Financial Accounting Standards Board (FASB), the Securities and Exchange Commission (SEC) and the Internal Revenue Service (IRS) are treating the accounting for cryptocurrency transactions.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-071-780-171-889, pop00319 tex.type: [object Object]
Keywords: dept.acc; peer-reviewed

The GAAP in Tesla’s earnings announcements: A case study on the proliferation of Non-GAAP financial measures - Aselta, James; Engel, Russell Paul (The Accounting Educators' Journal, 2019)
The reporting of non-Generally Accepted Accounting Principles Measures (non-GAAP) by U.S. publically traded companies is not new but it has recently come under increased scrutiny by the United States Securities and Exchange Commission (SEC). This case presents a specific example of this scrutiny in the form of Tesla, Inc.’s quarterly earnings announcements and Tesla’s subsequent correspondence with the SEC. This case requires students to answer relevant questions about GAAP vs Non GAAP reporting, generally in the form of a research memo, with references to applicable SEC regulations and guidance on the use and reporting of non-GAAP measures.
Citation Key Alias: lens.org/107-162-194-311-028, pop00324 tex.type: [object Object]
Keywords: dept.acc; peer-reviewed; ⛔ No DOI found

Is cash still trapped? - Aselta, James; Engel, Russell Paul; Lyons, Bridget; Pannese, Danny (Strategic Finance, 2019)
Keywords: dept.acc; peer-reviewed; ⛔ No DOI found